Empowerment of Processing Butterfly Flower (Clitoria ternatea) as Functional Food in the Tambulampot RW XI Group at Sumorame Candi Sidoarjo - Hudi, Lukman; Budiandari, Rahmah Utami; Prihatiningrum, Andriani Eko; Alhaq, Alfrina Nabila; Miranda, Wiji Amelia (UM Metro, 2024)
Abstract Telang flowers are one type of tambulampot plant that is widely cultivated. The butterfly pea flower (Clitoria ternatea) is a flower that comes from vines which is also known as the butterfly pea flower, blue flower, or butterfly pea flower. This flower contains compounds that can be used as natural dyes, especially to provide a blue or purple color to food or drinks. This flower contains anthocyanins, such as high concentrations of sinensetin and ternatin, which give the flower its blue color. Anthocyanins have antioxidant and anti-inflammatory properties that can protect body cells from oxidative damage. Clitoria ternatea flowers also contain flavonoids such as kaempferol and quercetin, which have antioxidant and anti-inflammatory properties similar to anthocyanins. Several types of alkaloids are found in Clitoria ternatea flowers, such as serotonin and coumarin, which can have a relaxing effect on the body and nervous system. Several studies show that Clitoria ternatea flower extract can help lower blood sugar levels. In the application of food products, Clitoria ternatea flowers can be used to make traditional telang tea drinks, cake and ice cream toppings, for food coloring and so on.